Business Process Reengineering in Indonesian Public Hospitals: A Multiple Case Study - Guruh Satriya; Mei Vita Ariyani; Melina Budiarti; Mira Veranita (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
Business Process Reengineering (BPR) represents a radical and fundamental strategy for improving organizational performance in healthcare settings, yet its implementation dynamics in Indonesian public hospitals remain insufficiently understood. This study employs a qualitative multiple case study design to explore how BPR is implemented across three Type B public hospitals in Indonesia, referred to pseudonymously as RS Alpha, RS Beta, and RS Gamma. Data were collected through 27 in-depth interviews with hospital directors, clinical department heads, administrative managers, and frontline healthcare staff, supplemented by document analysis and non-participant observation conducted over a six-month period. Thematic analysis following Braun and Clarke (2006) revealed four overarching themes: (1) enabling conditions for BPR adoption, (2) process redesign and IT integration challenges, (3) human resource dimensions of BPR implementation, and (4) organizational outcomes and sustainability of reengineered processes. Findings indicate that leadership commitment and change management capacity are pivotal determinants of BPR success, while resistance from clinical staff, inadequate IT infrastructure, and bureaucratic rigidity constitute the primary barriers. Cross-case comparison reveals that hospitals with stronger human resource development programs achieved more sustainable process improvements. The study contributes an empirically grounded, context-sensitive understanding of BPR in Indonesia's public health sector, with implications for hospital management and health system reform policy